High molecular weight caldesmon positive stromal cells in the capsule of thyroid follicular tumours and tumour-like lesions. Issue 12 (1st December 2002) - Nakayama, H; Enzan, H; Miyazaki, E; Moriki, T; Kiyoku, H; Toi, M; Kuroda, N; Hiroi, M
Abstract : Aims: To investigate the smooth muscle nature of the spindle stromal cells in the capsule of thyroid tumours and tumour-like lesions. Methods: Immunostaining for high molecular weight caldesmon (HCD), a highly specific marker for smooth muscle differentiation, was performed in 70 primary thyroid tumours and tumour-like lesions (21 hyperplastic nodules, 29 follicular adenomas, five minimally invasive follicular carcinomas, six widely invasive follicular carcinomas, and nine encapsulated papillary carcinomas). Results: HCD positive stromal cells (HCD+ cells) were detected in the capsule of 20 of the 21 hyperplastic nodules, and all of the 29 follicular adenomas and five minimally invasive follicular carcinomas, whereas HCD+ cells were seen in the capsule of only four of the six widely invasive follicular carcinomas and no HCD+ cells were seen in the capsule of the nine encapsulated papillary carcinomas examined. Conclusions: The presence of HCD+ cells in the capsule is characteristic of thyroid follicular tumours and tumour-like lesions. The stromal cells in the capsule of thyroid follicular tumours and tumour-like lesions are different from those of encapsulated papillary carcinoma.